2014
DOI: 10.1039/c3dt52554f
|View full text |Cite
|
Sign up to set email alerts
|

NO2bond cleavage by MoL3complexes

Abstract: The cleavage of one N-O bond in NO2 by two equivalents of Mo(NRAr)3 has been shown to occur to form molybdenum oxide and nitrosyl complexes. The mechanism and electronic rearrangement of this reaction was investigated using density functional theory, using both a model Mo(NH2)3 system and the full [N((t)Bu)(3,5-dimethylphenyl)] experimental ligand. For the model ligand, several possible modes of coordination for the resulting complex were observed, along with isomerisation and bond breaking pathways. The lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The N[ t Bu]Ph ligand is more relevant to the experimental ligand (eq ). The quartet Mo(NH 2 ) 3 (1_Q) is lower in energy than its doublet (1_D) by 58.2 kJ/mol, which is in accordance with earlier studies. ,,, Consequently, the reaction pathway will begin along the quartet surface, as the ground state for SO 2 is a singlet. The earlier studies have revealed that there are two different conceivable approaches for bond cleavage within small molecules: mononuclear and binuclear mechanisms.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The N[ t Bu]Ph ligand is more relevant to the experimental ligand (eq ). The quartet Mo(NH 2 ) 3 (1_Q) is lower in energy than its doublet (1_D) by 58.2 kJ/mol, which is in accordance with earlier studies. ,,, Consequently, the reaction pathway will begin along the quartet surface, as the ground state for SO 2 is a singlet. The earlier studies have revealed that there are two different conceivable approaches for bond cleavage within small molecules: mononuclear and binuclear mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…The nomenclature used in this paper is as follows: (i) N (numbers) represent minima and TS represent intraconversion transition structures; (ii) spin-states are denoted by S (singlet), D (doublet), T (triplet), Q (quartet), and Q T (quintet); (iii) breaking transition structures by TSB ; (iv) the N[ t Bu]Ph ligand is represented by the Ar script; and (v) the N[ t Bu]Ph ligands are oriented in an almost C 3 V , propeller-like arrangement, which has been reported as the most likely low-energy conformation …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.189(11) Å in (PPh 4 )[W( N -NO 2 )­(CO) 5 ]) . Similar energetic differences have been recently computed for nitrito and nitro isomers of [MoL 3 (NO 2 )] complexes (L 3 = triamide ligands), also revealing low kinetic barriers for the conversion between the different linkage isomers of the nitrite ligand …”
Section: Resultsmentioning
confidence: 94%
“…26 Similar energetic differences have been recently computed for nitrito and nitro isomers of [MoL 3 (NO 2 )] complexes (L 3 = triamide ligands), also revealing low kinetic barriers for the conversion between the different linkage isomers of the nitrite ligand. 27 Stereoselectivity in the Reactions of 1 and 2 with NO. We have investigated the selective formation of either cis or trans dinitrosyl complexes with the help of DFT calculations on some of the critical steps (see the Experimental Section and Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 97%